Signatures of meteor showers and sporadics inferred from the height distribution of meteor echoes. (15th September 2020) - Lukianova, Renata; Kozlovsky, Alexander; Lester, Mark
Abstract: The SKYiMET meteor radar is capable of measuring the height distribution of ionized meteor trails. Observations of the Sodankyla radar (67°N, 23°E) in 2008–2019 are analyzed. A method is applied, based on the median and quartiles of meteor heights, for distinguishing meteor showers from much more intense background sporadic meteors. Since the shower meteors are commonly less dense and enter the Earth's atmosphere at a larger velocity, they produce ionization up to 3 ​km higher than sporadic meteors. This effect manifests itself in the form of narrow peaks that are clearly visible in the median and quartiles of the meteor height. Seven established showers with zenith hourly rate (ZHR) ​> ​12 were identified. In addition, using both the height parameters and the radiant distribution, a signature of a former meteor stream evolving into sporadic meteors is found. This additional sporadic inflow has an antihelion source and occurs in the January. Highlights: Parameters of the vertical profile of daily meteor echoes from the Sodankyla (67N) SKYiMET meteor radar are calculated. The shower meteoroids produce ionization trails at considerably higher altitudes than the sporadic background. Simple and robust method for the recognition of the occurrence of shower meteors on the much more intense sporadic background is proposed. The radiant distribution reveals a signature of a dispersed meteor stream evolving into sporadics. This additional quasi-sporadic inflow occurring in the end of January, likely has a north toroidal source.